A Case of Emergency Cesarean Section with Pseudopregnancy - Rajab Dashti-Kalantar; Seyedeh Fatemeh Hosseini; Mozhgan Javadnoori (Mashhad University of Medical Sciences, 2021)
Background: Pseudopregnancy is a physical state whereby all the signs and symptoms of pregnancy are exhibited with the exception of the presence of a fetus. The detection of a pseudopregnancy is significant; however, as it may be associated with all pregnancy symptoms, it is important to differentiate between the two. Case report: We report a case of pseudopregnancy leading to an emergency cesarean section. A 28-year-old woman claiming a 7-month pregnancy was referred to a rural health center by her in-laws complaining of vaginal bleeding. The woman was referred to an urban hospital by emergency medical services with a diagnosis of placenta previa. In the hospital, she underwent an emergency cesarean section due to a severe deceleration of fetal heart rate (FHR), prior to assessing by an ultrasound. No fetus or signs of uterine or abdominal pregnancy was observed. Wrong auscultation of the maternal heart rate instead of FHR seemed to be the main error. Conclusion: It is required to pay more attention to the methods of differentiation of FHR from maternal heart rate. This report highlighted the significance of early detection of pseudopregnancy.